Child Friendly Education: Application of Child Friendly Schools in Creating School Culture in SDN 3 Pasirtamiang: Pendidikan Ramah Anak : Penerapan Sekolah Ramah Anak dalam Mewujudkan Budaya Sekolah di SDN 3 Pasirtamiang - Uswah, Fauziyatun Nurul; Dewi, Hestiana; Fathiyati, Teti Nurul (Proceedings of The ICECRS, 2020)
School is a place that should allow a child to learn and feel comfortable. But until now the school has not been able to be a friendly place for children. Although referred to as an educational institution, but violence actually often occurs in schools. Child Friendly Schools are educational units that are able to guarantee, fulfill, respect the rights of children, and protect children from violence, discrimination, and other mistreatment and support children's participation, especially in planning, policy, learning, and complaints mechanisms. Child Friendly Schools aim to protect and provide services that guarantee and protect children from physical and non-physical abuse. This study aims to determine whether schools have implemented Child Friendly Schools as a whole or are still not optimal. Know the school culture that is the result of Child Friendly Schools. The method used in this research is descriptive qualitative which will describe how the implementation of Child Friendly Schools in SDN 3 Pasirtamiang. Data collection techniques through observation, documentation, interviews and questionnaires. Data analysis method uses descriptive method. The results of research at SDN 3 Pasirtamiang have referred to the classification standards for child-friendly schools that have been declared by the ministry of education and culture based on the facts contained in the field. With the formation of character as a child-friendly school culture equips students to be able to actualize themselves towards Islamic character. To develop and create child-friendly schools, it is better to be able to integrate existing programs & activities and be able to adjust the situation, conditions, and abilities of the school by optimizing all school resources.